2016
DOI: 10.2320/jinstmet.j2016022
|View full text |Cite
|
Sign up to set email alerts
|

Current Status and Smelting Technologies of Rhenium

Abstract: Rhenium (Re) is used as additives in several alloys such as nickel based superalloys for jet engine turbine blades, platinum catalysts for oil refining, and thermocouples used at ultra high temperature, in order to improve strength and stability at high temperature. The demand of Re has been increasing with the increase in demand of the superalloys. In this article, current status such as demand and distribution of Re are reviewed, and smelting technologies for recovering Re from various ores are introduced.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…The methods of smelting the Re from the ore have been described in the reports of the authors. 14 and in the excellent reviews of Melaven, Lebedev, Davenport, Abisheva et al, Anderson et al, Millensifer et al, and Shen et al 6,36,45,48,61,70,71…”
Section: Rhenium Smelting Technologiesmentioning
confidence: 99%
See 3 more Smart Citations
“…The methods of smelting the Re from the ore have been described in the reports of the authors. 14 and in the excellent reviews of Melaven, Lebedev, Davenport, Abisheva et al, Anderson et al, Millensifer et al, and Shen et al 6,36,45,48,61,70,71…”
Section: Rhenium Smelting Technologiesmentioning
confidence: 99%
“…The methods of smelting the Re from the ore have been described in the reports of the authors. 14 6,36,45,48,61,70,71 History of rhenium production before its initial industrial use German scientists Walter Noddack, Ida Tacke, and Otto Berg reported the discovery of the 75 th element of the periodic table in 1925 and named it rhenium after the Rhine river (German: Rhein river). 72 After this discovery, Wilhelm Feit in Germany developed a method to extract Re from the Mo residues (which are mainly composed of Cu, Mo, Ni, Fe, V, and Re) extracted from Cu ores.…”
Section: Rhenium Smelting Technologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Рений -один из наиболее эффективных легирующих компонентов cуперсплавов [1][2][3][4][5][6][7][8][9], для получения которых используется более 80 % этого металла [9,10]. Многокомпонентные Re-содержащие сплавы 5-го поколения содержат ряд ценных редких и цветных металлов, таких как никель, хром, кобальт, вольфрам, тантал, молибден, гафний, титан, алюминий и рутений [9][10][11].…”
unclassified